The Role of the Major Superior with Particular Reference to Apostolic Women's Religious Institutes in the United States - Connors, Kelly (Université Saint-Paul / Saint Paul University, 2011)
This thesis seeks to clarify the nature of the office of the major superior of apostolic religious institutes of women in the United States. In it we explore how the current law of the Catholic Church defines the ministry of major superiors. This study looks at the various obligations and rights of the major superior and the ends toward which they move. In light of this research, we assess the tasks essential to the ministry of the major superior and then distinguish those things that belong properly to the office. We consider those tasks that can be and, for the sake of being able to attend to the essential elements, must be delegated. In reclaiming the office of major superior the mission of the religious institute will be promoted and therefore benefit the Church, the members, and the people of God. This study assesses the implications and applications of the role of major superiors on the life and administration of religious institutes and discerning potential governance models that will liberate them to be about the essential obligations of their office – preserving the unity of the institute, fidelity to the charism, promotion of the mission, and care of the members – while facilitating healthy participation of all the members in decision-making and exercising subsidiarity yet preserving the personal authority of the superior for the good of the whole. The challenge for women religious today is to acknowledge the bureaucracy of the systems of ordinary governance, glean that which is useful and fruitful for the life and mission of the institute, and bear witness to the gospel through a counter-cultural expression of a bureaucracy that is merely a means to a greater good and not an end in itself. In summary, we canonically, historically, and sociologically explore a combination of the exercise of authority, models of ordinary governance structures, and the role of the major superior as defined by ecclesiastical law. Our purpose is to evaluate how canon law defines the role of the major superior and how this definition informs the exercise and obligations of the office.
Keywords: Canon Law; Religious Law; Women Religious; United States Religious Life; Ordinary Governance; Structures of Governance; Models of Governance; Major Superiors; ecclesial documents on religious life; power and authority of the religious superior